“Not the Lover’s Choice, but the Poet’s”: Classical Receptions in Portrait of a Lady on Fire - Benjamin Eldon Stevens (Frontière·s)
Céline Sciamma’s film Portrait of a Lady on Fire (Portrait de la jeune fille en feu, 2019) tells its 18th-century story of love and loss in part by retelling an ancient story, the myth of the poet Orpheus and his beloved Eurydice, as related by the Roman poet Ovid in his epic Metamorphoses (c. 8 CE). The myth’s most iconic moment, when Orpheus turns around to look at Eurydice and therefore loses her to Hades, occupies a central position in the film’s plot and underlies its running theme of ‘looking at’ as ‘looking back.’ By changing certain aspects of the myth – replacing poetry or singing with painting, making both main characters women, and having them alternate between the two main mythic roles – Portrait does not so much update the ancient story as debate its meanings. What does it mean to lose someone beloved but gain their image? How is every loss a kind of death, and in its train, the life that remains a kind of afterlife? Most generally, what are the links among lived experience, memory, and art? By raising these questions via the ancient myth, Portrait meditates on the effect of making, as Orpheus did, “not the lover’s choice, but the poet’s.”